Mechanical energy and propulsion in ergometer double poling by cross-country skiers - Danielsen, J.; Sandbakk, O.; Holmberg, H. C.; Ettema, G. (Medicine & Science in Sports & Exercise, 2015)
Purpose: This study aims to investigate fluctuations in total mechanical energy of the body (Ebody) in relation to external ergometer work (Werg) during the poling and recovery phases of simulated double-poling cross-country skiing.